Fenomena Konversi Agama dalam Perspektif Agama Hindu dan Agama Islam: Studi Komperatif Terhadap Kehidupan Beragama - Musa, Tazkia Shuhaila; Sari Siregar, Husna (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
The phenomenon of religious conversion is a complex social and spiritual phenomenon that is often discussed in the religious life of society. This study aims to examine the dynamics of conversion from the perspective of Hinduism and Islam by highlighting the causal factors and the accompanying social and theological implications. The method used is the phenomenology of religion approach and analysis of religious texts from both religions. The results of the study show that religious conversion is not only influenced by spiritual motivation, but also by internal factors such as personality and psychology, as well as external factors such as the environment, marriage, and social pressure. The external factor that most influences religious conversion is interfaith marriage. In the Hindu view, conversion is considered a form of denial of dharma and has an impact on spiritual life and social rights, such as inheritance. Meanwhile, in Islam, the act of apostasy is considered a form of rejection of the teachings of monotheism, with different theological and legal consequences depending on the context. These findings emphasize the importance of a wise and tolerant approach in responding to religious conversion, as well as the need for a space for dialogue between religious communities to build mutually respectful understanding.